Relation of high resolution computed tomography findings with functionnal parameters in asthma and chronic obstructive pulmonary disease - Bahadır, Hakan; İkitimur, Hande and Akman, Canan and Mutlu, Birsen and Gemicioğlu, Bilun (Cerrahpaşa Medical Journal, 2019)
Objectives: We investigated in stable asthma and chronic obstructive pulmonary disease (COPD) cases, the comparison of HRCT scan abnormalities with the correlation of biometric and functional parameters. Methods: 29 nonsmoker asthma patients; average age 46.7 ± 14.6, and 20 smoker/ex-smoker COPD patients; average age 65.4 ± 10 were studied. The patients were stable during last three weeks and agreed to have HRCT and respiratory function tests. Results: There were no significant differences in the mean FVC and FEV1 parameters between two groups (p=0.498, p=0.198). But, FEV1/FVC and FEF25-75 decreased in COPD group (p<0.0001, p=0.016). 27.5%of asthma and 20% of COPD patients had normal HRCT findings during evaluation. 41,4%of asthma and 30% of COPD patients showed bronchial wall thickness. 27.6% of asthma and 40% of COPD patients had tubular bronchiectasis. 20.7% of asthma and 5% of COPD patients had air-trapping bronchiectasis. All those findings were not significant with X2 test, between two groups. Only statistically significant result was 13.8% of asthma and 60% of COPD patients had emphysema (p<0.001). Conclusion: We conclude that the statistical significance found for emphysema parameter is not important for the differentiation of two groups, as either asthma or COPD patients present similar remodeling patterns on HRCT scans.